Is infographic journalism? - Sousa, Ana Filipa Teixeira (2012)
Since the early 80s, with USA Today, computer graphics have gained prominence in journalism through the development of information systems / Information Technologies and Communication that potentiate the computerization of newsrooms making this process easier. Currently, the process of paradigm shift in which journalism is makes this question of the definition and delimitation of concepts imperative, becoming the computer graphics one of the main areas of relevance in discussion of the journalistic field. The question often posed by theorists and practitioners focuses in the veracity of the statement "infographics are, in fact, journalism". In this article we state that infographics have all the features that make it a fundamental part of journalism today, and on digital platforms, this form of communication may be an attractive element for readers' attention. In this sense, we expose the historical context and conceptual computer graphics applied to the press and digital platforms, stressing the added value of using computer graphics in online newspapers.